Seasonal variation in the phytoplankton of a saline lowland river (Buenos Aires, Argentina) throughout an intensive sampling period - Bazzuri, Maria Elisa (2010)
The aim of this survey was to analyse seasonal variations in phytoplankton composition and abundance with respect to temperature and conductivity values at two sampling sites in the Salado River's lower basin: El Destino and Guerrero. Samples were taken twice a week from 9 March 2004 to 20 July 2004. A total of 145 and 143 species were identified for these two sites, respectively. Infrequent species were discarded to avoid statistical misinterpretations. Autocorrelation analyses (Ljung‐Box Q‐statistic) were performed in order to establish seasonal patterns for species abundance. Similar significant (p < 0.05) autocorrelation patterns were observed for phytoplankton species composition, temperature and conductivity, thus, illustrating correlations with seasonal behaviour. On the basis of these data, species were grouped as (1) late‐summer: with 34 species well represented in warm waters (>22°C) (e.g. Planctonema lauterbornii and Chroococcus spp.); (2) winter: with 10 species that reached their highest densities in cold waters (<12°C) (e.g. Binuclearia eriensis and Microcystis firma); (3) transitional: of only four species with abundance peaks during intermediate conditions (15.5°C average) such as Closteriopsis acicularis and Nodularia spumigena and (4) independent: with 22 species of random behaviour whose autocorrelations remain within confidence limits. These four classifications pertain to species with similar presence at both sampling sites; the rest of the species evinced slightly different patterns. An apparent season‐associated succession of species was detected with those adapted to the warm, stagnant water of the late summer being replaced by others acclimated to the cold water of the winter.